Atypical Reversible Leucoencephalopathy Syndrome after Bevacizumab/Folfox Regimen for Metastatic Colon Cancer. (21st October 2014) - Salmi, Narimane; Elghissassi, Ibrahim; Bellahammou, Khadija; Lakhdissi, Asmaa; Mrabti, Hind; Errihani, Hassan
Abstract : We are reporting a case of multifocal reversible leucoencephalopathy syndrome induced by chemotherapy based on Folfox-Bevacizumab regimen. A 44-year-old female, with no history of hypertension, received a chemotherapy based on Folfox-Bevacizumab for her metastatic colon cancer (5 FU: 325 mg/m 2  d1 by intravenous infusion, Oxaliplatin 80 mg/m 2  d1, and Bevacizumab: 7.5 mg/Kg d1). During the fourth cure, she presented delirium, seizures, and visual disturbances. The computed tomography (CT) of the brain showed hypodense lesions of the white matter of frontal, parietal, and occipital lobes, which were bilateral and symmetrical. The clinical table was reversible under symptomatic treatment.